Effects of Antiretroviral Therapy on Sperm DNA Integrity of HIV-1-Infected Men. Issue 6 (November 2018) - Savasi, Valeria; Oneta, Monica; Laoreti, Arianna; Parisi, Francesca; Parrilla, Bina; Duca, Piergiorgio; Cetin, Irene
HIV-1-affected couples' desire to have children and free sexual intercourses with the use of pre-exposure prophylaxis for the negative partner has emerged as an alternative option to assisted reproduction in aviremic patients under highly active antiretroviral therapy (HAART). It is already known that sperm quality may be impaired in HIV-infected men. The underlying physiopathological mechanism is still debated. The aim of this study was to evaluate the effects of HAART on sperm DNA fragmentation, comparing HIV-1-infected patients taking HAART versus naïve HIV-1-infected patients. This is a prospective case-control study. Sperm nuclear DNA fragmentation rate was evaluated by the sperm chromatin dispersion test in 77 HIV-infected men: 53 HIV-1 patients receiving HAART (Group 1) versus 24 naïve HIV-1 patients not receiving HAART (Group 2). Complete semen analysis was performed according to WHO 2010 recommendations. Patients with HBV infection or HCV infection coinfections and genital tract infections wre excluded. All the patients did not present any clinical signs of their disease. Seminal parameters were examined in the two groups, showing no significant differences. Increased sperm DNA fragmentation > 30% was demonstrated in 67.9% of patients in Group 1 and 37.5% of patients in Group 2, respectively ( p = .02). A positive but nonsignificant trend toward increased fragmentation was reported with advancing patients' age. In conclusion, sperm nuclear fragmentation rate is increased in HIV-1-infected patients taking HAART compared to HIV-1 patients not receiving HAART.